Să se efectueze:

6+2•(2+6•2+13•5-5) =

6+6•[6-6•(6-6)]=

4+50:[2+24:(3•5-6•2)]-1=

12+3•[2+3•(3•4-6)]=

6•7+6•3+5•(7+3•2)=

6+5•[3+2•(2+3)] =

400-3•[2+5•3•(9-4)] =

26+3•4•[140-3•(2+4•3)] =

107•2+3[2•(3+5)•4+6•(5-3)]=

(6+3•5)•4-2•(5-3)=

6+6:[14-5:5•(16-8)+(4+4)]=

(10+10:10-0•10)•(10-0)

35+17•2+15•[3+2•2•(3+2•3)]=

(2•3+7)•(6+5•5)=

16+3•5+5•(2-1)•(7-7)=

3•(5+6•2)•(5•6+2)=

2+2•{2+2•[2+(2+2•2)]}=

6+5•{3+2•(2+5•4)+3•[2+6•(15-2•4)]}=

(3+2•9)•[6+5•7-3•(9-4•2)-204•(72-8•9)]=

7+2•13•{15-2•7+4•[3+2•3+6•3-(5+6•2)]}•4-4=

3+5•(7+4)+3•{6+5•2+[3+4•(3+4)+2•(6-2•2)+5]}=

{[1+(2+5•3)•4]+6+(7•8-9)}•(10-2)=

3+5•{6+2•[351:39-204:(3•5+19)]:6}=

657:73+5•{624:6:52+3[7-5•(6-10:2)]}=

24+6:2+3•[5:5+6-6:2+3•(5+5•5)]=

(64+4:4):[2+3:3+162:27-(3+2•18:9:2)]=